Exogenous melatonin improves cotton yield under drought stress by enhancing root development and reducing root damage - Lingxiao Zhu; Hongchun Sun; Ranran Wang; Congcong Guo; Liantao Liu; Yongjiang Zhang; Ke Zhang; Zhiying Bai; Anchang Li; Jiehua Zhu; Cundong Li (Journal of Integrative Agriculture, 2024)
The exogenous application of melatonin by the root drenching method is an effective way to improve crop drought resistance. However, the optimal concentration of melatonin by root drenching and the physiological mechanisms underlying melatonin-induced drought tolerance in cotton (Gossypium hirsutum L.) roots remain elusive. This study determined the optimal concentration of melatonin by root drenching and explored the protective effects of melatonin on cotton roots. The results showed that 50 μmol L−1 melatonin was optimal and significantly mitigated the inhibitory effect of drought on cotton seedling growth. Exogenous melatonin promoted root development in drought-stressed cotton plants by remarkably increasing the root length, projected area, surface area, volume, diameter, and biomass. Melatonin also mitigated the drought-weakened photosynthetic capacity of cotton and regulated the endogenous hormone contents by regulating the relative expression levels of hormone-synthesis genes under drought stress. Melatonin-treated cotton seedlings maintained optimal enzymatic and non-enzymatic antioxidant capacities, and produced relatively lower levels of reactive oxygen species and malondialdehyde, thus reducing the drought stress damage to cotton roots (such as mitochondrial damage). Moreover, melatonin alleviated the yield and fiber length declines caused by drought stress. Taken together, these findings show that root drenching with exogenous melatonin increases the cotton yield by enhancing root development and reducing the root damage induced by drought stress. In summary, these results provide a foundation for the application of melatonin in the field by the root drenching method.